A Comprehensive Exploration of the Holistic Healing Power of Yoga - Upadhya, Yammath (Journal of Rapti Babai Campus, 2025)
This article explores the healing power of yoga, an ancient practice that combines physical postures, meditation, breath work, self-reflection, and mantras. Originating in India, yoga is increasingly recognized for its therapeutic benefits in promoting overall health and well-being. It addresses not only physical health but also mental, emotional, and spiritual well-being, making it a holistic approach to healing. Scientific research has shown that regular yoga practice helps reduce stress, lower anxiety, and alleviate chronic pain. It enhances emotional balance, improves mood, and supports mental health by promoting mindfulness and self-awareness. Studies suggest that yoga can also aid in trauma recovery and improve cognitive function. The practice creates a sense of inner peace and supports spiritual growth, helping individuals connect with a deeper sense of self. Yoga’s therapeutic potential extends beyond mental and emotional health. It has been shown to boost natural immunity and assist in the body’s healing processes. By integrating physical movement with breath awareness and meditation, yoga promotes harmony between the body, mind, and spirit. While growing evidence supports yoga’s health benefits, further research is needed to fully understand the specific therapeutic mechanisms at play. Continued exploration will help unlock its full healing potential and cement its role as a complementary therapy for overall human well-being.